Leadership Development and Employee Engagement in Public Organizations: An Integrative Review - Abdul Rahman; Maksud Hakim (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This integrative review synthesizes evidence on how multi-component leadership development (training, coaching/mentoring, and structured feedback/action learning) shapes leader micro-behaviors that build employee engagement in public organizations and how engagement contributes to employee performance and public value. Methodology: We reviewed 30 peer-reviewed journal articles (2016–2025) retrieved from Scopus, Web of Science, ProQuest, Google Scholar, and publisher platforms. Studies were screened for public and quasi-public settings and retained only when a variable Digital Object Identifier (DOI) was available for them. Results: Four patterns emerged. First, bundled interventions are more likely to produce sustained behavioral transfer than stand-alone training. Second, micro-behavior’s goal clarification, coaching conversations, empowering delegation, inclusive voice, and ethical transparency create job resources, psychological safety, and trust that activate engagement. Third, engaged employees exhibit higher task and adaptive performance, thereby enhancing service quality, innovation, and reform implementation. Fourth, digital governance and transparency initiatives amplify the engagement–public value link when accountability routines and performance information are credible, but severe resource constraints weaken this translation. Conclusions: Leadership development should be designed as a continuous system embedded in work routines and evaluated using multilevel indicators from leader behavior change to engagement, performance, and public value. Limitations: This review was limited to English-language journal articles with DOI links and did not estimate pooled effect sizes. Contributions: This review proposes the Leadership Development-Engagement-Public Value (LDEP?V) model and research propositions to guide future testing in resource?constrained public organizations.